(untitled) (Fiep Bulletin - online, 2015)
Introduction: Cerebral palsy is characterized as motor dysfunction, due to non-progressive brain injury that occurs early in life. Objective: Verify the publications in the area of physiotherapy related to Equitherapy in cerebral palsy, analyzing the effectiveness of various methods of intervention. Method: Literature review, by means of research on Lilacs database and Neurosciências magazine, between April and June of 2014, using the key words "benefits", "Equitherapy" and "cerebral palsy". Criterion of inclusion were: articles promoting physiotherapy, published in Portuguese and related to the key words. Results: Out of the 30 articles initially found, 03 that served the criterion were included. With this study it was possible to observe the necessity for more research in neurology with additional and important techniques such as Equitherapy that helps the treatment of pathologies such as cerebral palsy. Conclusion: it was observed the apparent gains provided by Equitherapy as an intervention, complementing physiotherapy, as it explores the potential of the practitioner because the environment where it is held is stimulating and allows overcoming.